2013
DOI: 10.1002/jobm.201200557
|View full text |Cite
|
Sign up to set email alerts
|

Human methicillin‐sensitive Staphylococcus aureus biofilms: potential associations with antibiotic resistance persistence and surface polysaccharide antigens

Abstract: The development of persistent antibiotic resistance by human methicillin-sensitive Staphylococcus aureus (MSSA) strains and substantial association with poly-N-acetyl glucosamine (PNAG) in biofilms is reported in this investigation. Sixteen of 31 MSSA strains under study were found to have developed resistance to one or more antibiotics, with four strains, two of which did not produce biofilms, showing resistance to cefoxitin, undetectable by mecA amplification. Antibiotic resistance displayed by 13/14 biofilm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 32 publications
0
15
0
Order By: Relevance
“…aureus . Biofilms are defined as complex communities of bacteria encased in an extracellular polymeric matrix and biofilm formation is believed to contribute to bacterial virulence, reduced susceptibility to antibiotics [ 13 15 ] and reduced clearance by the immune system. Despite the plethora of studies examining the involvement of biofilm formation [ 16 ] and/or single virulence factors [ 17 , 18 ] in e.g.…”
Section: Introductionmentioning
confidence: 99%
“…aureus . Biofilms are defined as complex communities of bacteria encased in an extracellular polymeric matrix and biofilm formation is believed to contribute to bacterial virulence, reduced susceptibility to antibiotics [ 13 15 ] and reduced clearance by the immune system. Despite the plethora of studies examining the involvement of biofilm formation [ 16 ] and/or single virulence factors [ 17 , 18 ] in e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Carbohydrates and surface proteins involved in adherence are known to be important in the EPS matrix and biofilm establishment (Toledo‐Arana et al ., ; Hall‐Stoodley et al ., ; Vergara‐Irigaray et al ., ). Poly‐β (1,6)‐N‐acetyl‐ d ‐glucosamine (PNAG) is a surface polysaccharide involved in biofilm accumulation and evasion of the host immune system in S. aureus and S. epidermidis (Izano et al ., ; Babra et al ., ), and it has been demonstrated that dispersin B, a PNAG‐degrading enzyme, was capable of detaching S. epidermidis biofilm, while DNase I primarily affected S. aureus biofilms (Izano et al ., ). Our data suggest that multiple EPS components need to be targeted to effectively disrupt biofilms.…”
Section: Discussionmentioning
confidence: 99%
“…The plates were washed two times with distilled water and dried, then washed using 95% ethanol, and the optical density was determined using a microtiter plate reader at 570 nm (iMark Microplate Reader Sigma-Aldrich, Japan). Based on OD the isolate was referred to as weak (OD=0.480), moderate (OD=0.720) and strong (OD>0.720) biofilm producers (Babra et al 2014).…”
Section: Biofilm Assay By Microtitre Plate (Mtp)mentioning
confidence: 99%
“…Compared to other pathogenic strains (MRSA) infections caused 20% death of all infections (Boucher and Corey, 2008). The resistivity of S. aureus infections is dependent on several factors among them, the most important factor is the ability of this organism to form biofilms (Babra et al, 2014).…”
Section: Introductionmentioning
confidence: 99%